Enhancing segmental compatibility and tuning the structure-property relationship in ferrocenylsilane tethered polyurethane. (9th September 2020) - Dhara, Moumita; Giri, Nitai; Dutta, Arunava; Patra, A.K.; Sastry, P.U.; Ingole, Mahesh Shrikishan; Jana, Tushar
Abstract: This article addresses the effect of enhanced segmental mixing on various physical properties of ferrocenylsilane tethered polybutadiene based polyurethane (PU). To study this, 2-(ferrocenylpropyl) dimethylsilane (FPDS) has been grafted to the pendant vinyl double bond of hydroxyl terminated polybutadiene (HTPB) and 2, 4-dinitrobenzene attached HTPB (HTPB-DNB) through hydrosilylation reaction and then this resulting diols (FPDS- g -HTPB and FPDS- g -HTPB-DNB) were polymerized with isophorone diisocyanate (IPDI) to obtain FPDS- g -HTPB-PU and FPDS- g -HTPB-DNB-PU. Spectral (NMR, IR) analysis, molecular weight measurements and estimation of free hydroxyl contents were carried out to confirm the formation of these new diols. The careful variation of the grafting condition altered the extent of FPDS tethering on the diols which resulted varying amount of Si and Fe contents in these modified HTPBs. Density functional theory (DFT) calculation revealed the presence of various interactions of Si with various functionalities including ferrocene of the chain which resulted highly cross-linked polymer matrix. Cyclic voltammetry (CV) measurements of FPDS- g -HTPB-DNB displayed non-Nerstain reversible redox system with slow electron transfer process owing to the presence of DNB. Further, the PUs obtained from these HTPBs were prepared and characterized thoroughly in terms of thermal, mechanical, structural and tensile properties to study the segmental mixing between hard and soft segments of PUs owing to the presence of Si, Fe and DNB in the PU chain. Higher degree of segmental mixing was noticed when Si, Fe in the diol increased and also presence of DNB in the diol played a significant role in inducing the segmental mixing. The co-existence of segmental mixing and phase separation has been confirmed by small-angle x-ray scattering studies which further reaffirmed by FESEM analysis. Finally, composite solid propellants (CSPs) were prepared from these modified HTPBs and burn rate measurements were carried out. We found that CSPs obtained from FPDS- g -HTPB-DNB displayed ~10% higher burn rate than the CSP made from bare HTPB-DNB. Graphical abstract: Image 1 Highlights: Ferrocenylsilane derivative tethered metallo polyurethane (MPU) synthesized. Presence of active Si causes extra crosslinking in the MPU. Enhanced segmental compatibility helps to improve mechanical of MPU.